Sodium reduction in emulsion-type sausage - Skogsberg, Lisa (SLU/Dept. of Food Science, 2016)
Sodium chloride (salt) is consumed in varying amounts between individuals and popula-tions worldwide, but the consumption is generally higher than the recommended intake in many parts of the world. Research has shown that high sodium consumption is associated with increased blood pressure and we are therefore recommended to consume less sodium. Meat and meat products are a group of products that contribute to a large amount of sodium in the diet. Therefore it is relevant to develop low sodium alternatives in this product segments. Two batches of three emulsion-type sausages with different level of substitution from sodium chloride to potassium chloride were manufactured in cooperation with a local company specialized in meat products (Andersson & Tillman, Uppsala, Sweden). The sausages produced had 0%, 15% and 30% degree of substitution with KCl on molar basis from the total of 2 g NaCl / 100g sausage. No difference could be observed between product types for moisture content, water ac-tivity, yield, color, pH and texture after Benjamini-Hochberg adjustment for false discov-ery rate. Consumer acceptance was lower for the 30% substitution sausage compared to the other sausage types. These results are however confounded by the fact that the 30% substitution batch used for sensory evaluation had softer texture, most likely due to production variability. It is likely that parameters other than the sodium content, such as variation in ingredients, temperature of production or pH have bigger impact on the sausage properties than the substitution of sodium chloride to potassium chloride. Consumers also showed great interest in buying low-sodium sausages if available on the market. There is market potential for the product segment of low-sodium sausages and there is technological potential of producing a sausage with low sodium content by replacing 30% of sodium chloride with potassium chloride, however, the sensory aspects need further studies.